Comparing Hospital and Primary Care Physicians' Attitudes and Knowledge Regarding Antibiotic Prescribing: A Survey within the Centre Region of Portugal - António Teixeira Rodrigues; João C. F. Nunes; Marta Estrela; Adolfo Figueiras; Fátima Roque; Maria Teresa Herdeiro (MDPI AG, 2021)
Background: Antibiotic resistance is a worldwide public health problem, leading to longer hospital stays, raising medical costs and mortality levels. As physicians' attitudes are key factors to antibiotic prescribing, this study sought to explore their differences between primary care and hospital settings. Methods: A survey was conducted between September 2011 and February 2012 in the center region of Portugal in the form of a questionnaire to compare hospital (n = 154) and primary care (n = 421) physicians' attitudes and knowledge regarding antibiotic prescribing. Results: More than 70% of the attitudes were statistically different (p < 0.05) between hospital physicians (HPs) and primary care physicians (PCPs). When compared to PCPs, HPs showed higher agreement with antibiotic resistances being a public health problem and ascribed more importance to microbiological tests and to the influence of prescription on the development of resistances. On the other hand, PCPs tended to agree more regarding the negative impact of self-medication with antibiotics dispensed without medical prescription and the need for rapid diagnostic tests. Seven out of nine sources of knowledge's usefulness were statistically different between both settings, with HPs considering most of the knowledge sources to be more useful than PCPs. Conclusions: Besides the efforts made to improve both antibiotic prescribing and use, there are differences in the opinions between physicians working in different settings that might impact the quality of antibiotic prescribing. In the future, these differences must be considered to develop more appropriate interventions.